Study of the distribution of Elphidium aff. poeyanum (D’ORBIGNY) and Buccella peruviana (D’ORBIGNY) from the Colorado basin (South America): Holocene paleoenvironmental inferences - Bernasconi, Emiliana (2015)
Benthic foraminiferal assemblages recovered from T1 core samples of the Colorado basin, in the continental margin of southeastern Argentina, were analyzed to understand their distribution patterns and ecological preferences. The foraminiferal assemblages showed two well-represented species: Elphidium aff. poeyanum (d’Orbigny) and Buccella peruviana (d’Orbigny), among others of very low proportion. Statistical analyses allowed identifying positive correlations between the abundance of E. aff. poeyanum and silt content and between B. peruviana and the sand content, reflecting better conditions for the development of both species. From a paleoenvironmental point of view, the assemblages recorded are characteristic of an inner shelf, showing a passage from typical shallow waters to normal marine conditions; such a passage represents a rise in the sea level during the post-last glacial maximum transgression. The results obtained contribute to the knowledge of South American foraminifers and paleoenvironments during the Holocene.